2015
DOI: 10.5966/sctm.2015-0039
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Therapeutic Potential of Mesenchymal Stem Cells and Limbal Epithelial Stem Cells for Ocular Surface Reconstruction

Abstract: Corneal regeneration x Stem cell-based therapy ABSTRACTStem cell-based therapy has become an attractive and promising approach for the treatment of severe injuries or thus-far incurable diseases. However, the use of stem cells is often limited by a shortage of available tissue-specific stem cells; therefore, other sources of stem cells are being investigated and tested. In this respect, mesenchymal stromal/stem cells (MSCs) have proven to be a promising stem cell type. In the present study, we prepared MSCs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 40 publications
(66 reference statements)
6
78
0
6
Order By: Relevance
“…Our research group and others have demonstrated that AT‐MSCs express corneal epithelial markers under basic culture conditions, suggesting that these cells may have some inherent properties to regenerate the corneal epithelium . In experimental models of LSCD, administration of AT‐MSCs subconjunctivally , topically , or overlaid on scleral contact lenses or nanofiber scaffolds promotes regeneration of the corneal epithelium. Additionally, a case report in which AT‐MSCs were applied topically to a patient with persistent sterile epithelial defects supports the potential benefit of this modality .…”
Section: Introductionmentioning
confidence: 78%
“…Our research group and others have demonstrated that AT‐MSCs express corneal epithelial markers under basic culture conditions, suggesting that these cells may have some inherent properties to regenerate the corneal epithelium . In experimental models of LSCD, administration of AT‐MSCs subconjunctivally , topically , or overlaid on scleral contact lenses or nanofiber scaffolds promotes regeneration of the corneal epithelium. Additionally, a case report in which AT‐MSCs were applied topically to a patient with persistent sterile epithelial defects supports the potential benefit of this modality .…”
Section: Introductionmentioning
confidence: 78%
“…For these reasons, alternative cell sources able to differentiate into the corneal epithelium have been tested for restoration of the corneal surface and wound healing. These include cultured oral mucosal epithelium, hair follicle, conjunctival and epidermal epithelium, amniotic epithelial cells, umbilical cord lining epithelial cells, as well as mesenchymal stem cells (MSCs) from adipose tissue, bone marrow, orbital fat, and immature dental pulp . Cultured autologous oral mucosal epithelium has been used clinically; again, most frequently, for chemical burns, although with somewhat lower success rates than with LESC transplantation (close to 70%) .…”
Section: Stem Cells For Epithelial Wound Healingmentioning
confidence: 99%
“…Cultured autologous oral mucosal epithelium has been used clinically; again, most frequently, for chemical burns, although with somewhat lower success rates than with LESC transplantation (close to 70%) . Most other cell types have only been examined in preclinical models .…”
Section: Stem Cells For Epithelial Wound Healingmentioning
confidence: 99%
“…97 BMSCs and limbal epithelial stem cells are similarly efficacious for treating limbal cell deficiency after alkali burn. 98 The ability of BMSCs to treat LSCD is attributed not only to transdifferentiation, but also to suppression of local inflammation and secretion of growth factors, thereby supporting the growth of residual corneal epithelial cells. 98 The use of MSCs for treating corneal diseases has recently been reviewed by our group, and the discussion below focuses primarily on the use of MSCs for treating inflammatory response in the ocular surface (Figure 4).…”
Section: Therapeutic Potential Of Mesenchymal Stem Cellsmentioning
confidence: 99%